Violence against women: a comparative legal study - Muhammad Husni, Ahmad; Mohammad, Abdul Basir; Mohd Nor, Amir Husin; Laluddin, Hayatullah; Samuri, Mohd. Al Adib (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
Domestic violence is a phenomenon that is widespread in modern society. Although, no extensive study has been undertaken so far to highlight the extent and proportion of the domestic violence in the Muslimsociety, its traces began to emerge,indicating the rise in the rate of domestic violence in the Islamic society. Consequently,all parties in the community are required to act urgently in solving the issue of domestic violence before it is too lateto stop it.Both conventional law and shari’ahare consulted to find the ground for adopting the harshest measures against those committing such a crime hence, deterring them from involvement in such violence.The study uses analytical and comparative approaches to elucidatethe justifications of both systems for adopting certain measures for dealing with domestic violence and to highlight the dimensions of their differences in respect of dealing with the issue. The aim of this study is to providean analytical discussion of domestic violence committed against women in a clear crystal manner. This is done in the light of relevant rules and provisions pertaining to human rights contained in both conventional and Islamic laws. The findings of the study shows that domestic violence has severe repercussionsfor household as it result in disintegration of family, lack of confidence and the feeling of insecurity hence, leading to destruction of institution of family and the emergence of psychological problems with the resultant criminal behaviors.